Aspectos relevantes da importância do bem-estar animal na suinocultura - Moraes, Deina Lima de (Universidade Federal do Tocantins, 2023)
The care and well-being of sows and piglets in the maternity phase is a theme to be addressed in this work. This is a literature review that aims to discuss the importance of adopting measures that promote better conditions of well-being and quality of life for these animals. Given the need for management that is consistent with its creation for commercial purposes, it is observed that some practices typical of the animal's nature are supplanted in the creation process, with the aim of making productivity and economic gains feasible for the producer. However, it is important to point out that measures that bring a high level of stress to the animal are increasingly being debated by professionals in the area, and their solutions have been investigated with the aim of ensuring this, a more pleasant and better coexistence quality of life in the farm environment. In this sense, it is essential to understand the importance and promotion of well-being during the rearing of the sows and their litters, aiming to point out ways that endorse the practice of treatment and management, closer to the natural habitat of these animals.